PEMIDANAAN PALING SINGKAT PELAKU TINDAK PIDANA KORUPSI DI PENGADILAN TINDAK PIDANA KORUPSI PADA PENGADILAN NEGERI PEKANBARU - Rizadi, Nadila; Indra, Mexsasai; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Corruption is one particular crime that is serious, organized that has caused serious problems and threats, because it can endanger the stability and security of the country. In eradicating criminal acts of corruption, judges as law enforcers have the power of the judiciary to hold justice in order to uphold law and justice by recognizing the principle of free and impartial justice. In imposing a sentence the judge is free in searching for the sentence that was handed down to the accused properly. In the context of the judge's freedom to determine the severity of the sentence where he can move within the maximum limits of the sentence or to choose the type of sentence, it can be stressed that these reasons, both made the basis for the burden of the sentence or to ease it. In its application, judges tend to impose corruption cases with minimal punishments both in Article 2, Article 3 and Article 12 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Eradication of Corruption.The purpose of writing this thesis, namely; First, knowing the conviction for perpetrators of corruption under Law Number 31 of 1999 concerning Eradication of Corruption in the Corruption Court at the Pekanbaru District Court, Second; find out that judges tend to impose the shortest criminal sentences of corruption perpetrators in the Corruption Court at the Pekanbaru District Court.From the results of the research based on two problem formulations it can be concluded, First, in the implementation of judges, the criminal act of corruption is in accordance with the provisions of the applicable law. As the basis for the judge in deciding a case of corruption is referring to Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning Eradication of Corruption Acts as material law and Act Number 8 of 1981 concerning Criminal Procedure Law as formal criminal law, as well as Law Number 48 of 2009 concerning Judicial Power. Second, in the implementation of criminal punishment for perpetrators of corruption under Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning Eradication of Corruption. Criminal is known as the shortest and longest. Which stipulations regarding criminal sanctions in the Act are relatively none that are formulated extraordinary (extraordinary) either related to the severity or related to the type of criminal. So that we can see the legal culture of judges and the paradigm of judges thinking in passing verdicts. In the legal culture of judges there are 3 typologies: first Judge typology (1): Positivistic and Nonpositivistic, second Judge typology (2): Textual and Contextual, third Judge typology (3): Materialist, Pragmatic, and Idealist.Keyword : Criminal Act, Corruption, Criminalization